Analysis of Boarding House Entrepreneurs' Perception of Hotel Tax Implementation in Batuceper District, Tangerang - Rulandari, Novianita; Novita, Dian (Sinergi International Journal of Accounting and Taxation, 2023)
This study aims to determine the perception of boarding house business owners, positive perceptions for boarding house entrepreneurs towards the implementation of hotel tax in Batuceper sub-district Tangerang, negative perceptions for boarding house entrepreneurs towards the application of hotel tax in Batuceper sub-district Tangerang. This type of research is qualitative research. Data collection techniques use observation, interviews and documentation. Data analysis techniques use triangulation, data reduction, data presentation, and data verification. The results showed that the perception of boarding house owners in Batuceper District regarding socialization carried out by the local government was not evenly distributed so that the information obtained by boarding house business owners was still unclear and resulted in a lack of understanding related to the tax, the fairness of tax rates was considered burdensome for owners and tenants, tax objects were considered unfair and appropriate so that they could cause tax avoidance actions, The self-assessment mechanism has been effective, but cooperation with all parties involved in implementing this tax is needed, and the quality of service has not been met and there are still complaints and criticisms from boarding house business owners. The convenience and ease of paying taxes is a progress that needs to be improved so that taxpayers, especially boarding house owners, can pay taxes anywhere and anytime.